AMS 14C Dating of the Cremated Human Bones and Funeral Fuel of the Western Balts. In Theory and in Practice - Shiroukhov, Roman (Archaeologia Lituana, 2019)
The article is dedicated to the application of AMS 14C dating method of cremated bones and samples of related charcoal, which is rather new for the East Baltic region. The data of 3 Western Balts cemeteries from Lithuania are analysed. Results of radiocarbon dating are compared to the estimated typological chronology of the artefacts. The OxCal simulation is applied in order to obtain the most probable dates. The study lays the foundation for further spatial and static analysis of selected data.